Starch grafted degradable water-absorbing material for sanitary products and method for preparing the same
Patent Information
- Application Number
- CN202611427339.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-16
AI Technical Summary
现有淀粉基吸水树脂仍存在明显短板:常规接枝体系富含羧基电离基团,在生理盐水环境下,盐离子对分子链电荷产生屏蔽,抑制聚电解质溶胀作用,分子链发生蜷缩收缩,树脂耐盐保水能力显著下降;单纯依靠化学交联形成的水凝胶表层强度不足,穿戴受压时网络易变形,液体容易反向渗出,产品干爽性达不到使用标准
本发明通过引入由衣康酸酐与含醇羟基的磺基甜菜碱发生开环酯化反应制得的两性功能单体,为共聚体系引入了特有的甜菜碱两性离子结构,该结构能够有效削弱高分子吸水树脂的聚电解质效应,提升材料在盐水环境下的吸液与保液能力;将双醛微晶纤维素分散于淀粉接枝共聚物网络中,利用其表面的醛基位点与壳聚糖分子链上的氨基发生反应,形成席夫碱共价键,从而有助于提高壳聚糖层与主体之间的结合牢固度,降低壳聚糖在吸液溶胀过程中的脱落,同时有利于维持凝胶表层的结构稳定性,所述壳聚糖层不仅维持了凝胶网络在受压状态下的结构稳定性,还大幅降低了材料受压后的水分反向渗透,降低其模拟返渗量,能够有效满足卫生用品对干爽性的严苛要求;以天然淀粉作为接枝共聚物骨架,并引入双醛微晶纤维素和壳聚糖等天然多糖组分,使材料在受控堆肥条件下具备最终需氧生物分解能力,满足了卫生用品绿色环保、可降解的应用需求;采用了“室温晾干、40℃真空干燥、60℃热风干燥”的三段式分级干燥工艺,该工艺有效避免了传统单一高温烘干容易引发的凝胶表面快速失水结皮及内部孔道坍塌问题,同时有效减少了高温对新形成的化学键的破坏,提高了吸水材料的综合吸液指标
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer absorbent materials technology, specifically to a starch-grafted biodegradable absorbent material for hygiene products and its preparation method. Background Technology
[0002] The core functional material of disposable hygiene products such as diapers and sanitary napkins is superabsorbent polymer (SAP). Currently, most mainstream products use petroleum-based polyacrylic acid resins, which have excellent absorbency but are difficult to biodegrade, leading to environmental pollution from waste. Therefore, developing bio-based biodegradable absorbent materials is an important direction for the industry. Existing starch-based SAPs still have significant shortcomings: conventional grafting systems are rich in carboxyl ionization groups. In a saline environment, salt ions shield the molecular chain charge, inhibiting polyelectrolyte swelling, causing the molecular chains to shrink and significantly reducing the resin's salt resistance and water retention capacity; the surface strength of hydrogels formed solely by chemical cross-linking is insufficient, and the network easily deforms under pressure during wear, leading to easy backflow of liquid and failure to meet product dryness standards. While there are reports of modifications using sulfonic acid monomers and modified cellulose, a complete solution that simultaneously achieves salt resistance, pressure-based liquid retention, strong chitosan support, and protection of the pore structure has not yet been developed, making it difficult to simultaneously meet the comprehensive requirements of hygiene products for absorbency, dryness, and biodegradability. Therefore, developing a starch-grafted water-absorbing material that combines excellent liquid absorption and water retention capacity, low backflow, strong component bonding, and biodegradability has become an urgent technical problem to be solved. Summary of the Invention
[0003] In order to overcome the shortcomings of the prior art, the present invention aims to provide a starch-grafted biodegradable absorbent material for hygiene products and its preparation method. The absorbent material prepared by the present invention has good free swelling absorption rate of deionized water, free swelling absorption rate of physiological saline, pressure absorption capacity and biodegradability.
[0004] To achieve the above objectives, the present invention provides the following technical solution: a starch-grafted biodegradable absorbent material for hygiene products, the absorbent material comprising a starch-grafted copolymer body and a chitosan layer distributed on the surface of the body; The starch graft copolymer is formed by free radical graft copolymerization of raw materials including natural starch, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid and amphoteric functional monomers to form a cross-linked network, and the dialdehyde microcrystalline cellulose is dispersed in the cross-linked network in the form of particles; The amphoteric functional monomer is the ring-opening esterification product of itaconic anhydride and sulfobetaine containing an alcohol hydroxyl group; The raw materials for preparing the absorbent material include, by weight: 20-30 parts of natural starch, 35-50 parts of acrylic acid, 8-15 parts of 2-acrylamido-2-methylpropanesulfonic acid, 1-3 parts of amphoteric functional monomer, 2-6 parts of dialdehyde microcrystalline cellulose, and 0.5-2 parts of chitosan.
[0005] The chitosan layer is distributed on the surface of the main body after being treated with a chitosan solution; the absorbent material undergoes a three-stage drying process after being treated with the chitosan solution, the three-stage drying process including: air drying at room temperature for 1-2 hours, vacuum drying at 40℃ for 4-6 hours, and hot air drying at 60℃ to constant weight; the vacuum degree of the 40℃ vacuum drying is -0.08 to -0.095 MPa, the wind speed of the 60℃ hot air drying is 1.0-2.0 m / s, and the constant weight is the difference between two adjacent weighings not exceeding 0.1%.
[0006] Furthermore, the natural starch is selected from at least one of tapioca starch, corn starch, and potato starch.
[0007] Furthermore, the preparation method of the hermaphroditic functional monomer is as follows: Step 1: Dissolve N,N-dimethylethanolamine in isopropanol solvent, add 1,3-propanesulfonic acid lactone dropwise under stirring, react at 40-50℃ for 6-12h, after the reaction is completed, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxysulfobetaine intermediate. Step 2: Add itaconic anhydride and terminal hydroxy sulfobetaine intermediate to N,N-dimethylformamide solvent, mix well, then add anhydrous sodium acetate, and react at 60-65℃ for 6-8 hours. After the reaction is completed, distill under reduced pressure, wash and dry to obtain the amphoteric functional monomer.
[0008] Further, in step one, the molar ratio of N,N-dimethylethanolamine to 1,3-propanesulfonic acid lactone is 1:(1.0-1.15); in step two, the molar ratio of itaconic anhydride to the terminal hydroxy sulfobetaine intermediate is 1:(0.8-1.2); and in step two, anhydrous sodium acetate is added as a catalyst, the amount of which is 10.0%-15.0% of the mass of itaconic anhydride.
[0009] Furthermore, the dialdehyde microcrystalline cellulose is prepared by oxidizing microcrystalline cellulose powder (D50≤20μm) with sodium periodate at pH 3.8, and the mass ratio of microcrystalline cellulose to sodium periodate is 1:(0.5-1). The aldehyde content of the dialdehyde microcrystalline cellulose is 5.2-6.8mmol / g.
[0010] Furthermore, the preparation method of the starch-grafted biodegradable absorbent material for hygiene products includes the following steps: (1) Preparation of mixed monomer solution: Mix acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid with a neutralization degree of 65%-75% with the amphoteric functional monomer evenly; (2) Graft copolymerization: Natural starch is gelatinized at 70-95℃ for 20-40 min, then cooled to 40-65℃, an initiator is added, and then the mixed monomer liquid and the suspension containing the dialdehyde microcrystalline cellulose and the chemical crosslinking agent are added dropwise. The mixture is reacted at 40-65℃ for 2-4 h to obtain a polymer hydrogel. (3) Chitosan anchoring and drying: The polymer hydrogel is cut into pieces, dehydrated, and then immersed in a chitosan solution. After immersion, a three-stage drying process is carried out. The three-stage drying process includes air drying at room temperature for 1-2 hours, vacuum drying at 40°C for 4-6 hours, and hot air drying at 60°C until constant weight. The vacuum degree of the 40°C vacuum drying is -0.08 to -0.095 MPa, the wind speed of the 60°C hot air drying is 1.0-2.0 m / s, and the constant weight is the mass difference between two adjacent weighings not exceeding 0.1%, thus obtaining the finished water-absorbing material.
[0011] Further, in step (2), the solvent of the suspension is deionized water; the chemical crosslinking agent is N,N'-methylenebisacrylamide, and its amount accounts for 0.05%-0.15% of the total mass of the mixed monomers.
[0012] Further, the chitosan solution is an aqueous solution of acetic acid with a chitosan mass concentration of 0.5%-1.0%, wherein the acetic acid mass concentration is 0.5%-2.0%, and the solution pH is 4.5-5.5; the immersion time in the chitosan solution is 1-4 hours, and the immersion temperature is room temperature; the viscosity-average molecular weight of the chitosan is 50,000-200,000, and the degree of deacetylation is ≥85%.
[0013] Further, in step (3), the dehydration treatment is: after cutting the polymer hydrogel into pieces, immerse it in anhydrous ethanol to dehydrate it, so that the water content of the gel is reduced to 50%-70%.
[0014] Furthermore, the moisture content is the wet basis moisture content, calculated by the following formula: wet basis moisture content = (wet sample mass - oven-dry sample mass) / wet sample mass × 100%.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: This invention introduces an amphoteric functional monomer, obtained by ring-opening esterification of itaconic anhydride and sulfobetaine containing alcohol hydroxyl groups, into the copolymer system, introducing a unique betaine zwitterionic structure. This structure effectively weakens the polyelectrolyte effect of superabsorbent polymers, improving the material's liquid absorption and retention capacity in saline environments. Furthermore, by dispersing dialdehyde microcrystalline cellulose in a starch graft copolymer network, the aldehyde sites on its surface react with the amino groups on the chitosan molecular chains to form Schiff base covalent bonds. This helps improve the bonding strength between the chitosan layer and the substrate, reducing chitosan shedding during liquid absorption and swelling, and simultaneously maintaining the structural stability of the gel surface. The chitosan layer not only maintains the structural stability of the gel network under pressure... Qualitative analysis significantly reduces the reverse water permeation of the material under pressure, lowering its simulated backflow rate and effectively meeting the stringent dryness requirements of hygiene products. Using natural starch as the graft copolymer backbone and introducing natural polysaccharide components such as dialdehyde microcrystalline cellulose and chitosan, the material possesses ultimate aerobic biodegradation capability under controlled composting conditions, meeting the green, environmentally friendly, and biodegradable application requirements of hygiene products. A three-stage graded drying process—room temperature air drying, 40℃ vacuum drying, and 60℃ hot air drying—effectively avoids the rapid water loss and crusting of the gel surface and the collapse of internal pores that are easily caused by traditional single high-temperature drying. Simultaneously, it effectively reduces the damage of newly formed chemical bonds caused by high temperatures, improving the overall liquid absorption index of the absorbent material. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] The reagents used in the following specific embodiments are of analytical grade. Additionally: Chitosan: viscosity-average molecular weight of 100,000, degree of deacetylation ≥85%.
[0018] The preparation method of dialdehyde microcrystalline cellulose is as follows: Weigh two portions of dried microcrystalline cellulose, 130g each, and place them in the ball jar of a ceramic vibrating ball mill. Turn on the ball mill at room temperature and ball mill for 24 hours. After ball milling, remove the sample and store it in a sealed bag for later use. Weigh 5g of the oven-dried microcrystalline cellulose ultrafine powder that has undergone the above ball milling treatment for 24 hours, place it in a 250mL three-necked round-bottom flask, add 100mL of distilled water (solid-liquid ratio 1:20, g / mL), and place it in a constant temperature water bath. Add sodium periodate at a mass ratio of 1:1 (microcrystalline cellulose ultrafine powder to sodium periodate), adjust the pH to 3.8, and react at 25℃ under light-protected and nitrogen-protected conditions for 4 hours. After the reaction is complete, add 0.1mol / L ethylene glycol aqueous solution and continue the reaction for 0.5 hours to remove unreacted sodium periodate. The reaction products were washed with distilled water and anhydrous ethanol, respectively, and dried to remove ethylene glycol and reaction byproducts. The processed dialdehyde microcrystalline cellulose ultrafine powder was then stored in a sealed bag for later use. The aldehyde content of the obtained dialdehyde microcrystalline cellulose was determined to be 5.2-6.8 mmol / g by the hydroxylamine hydrochloride method.
[0019] In each embodiment, the amount of water used for starch gelatinization was calculated based on a starch mass concentration of 10%-15%. In each embodiment, the starch was stirred evenly at room temperature and then heated to a set temperature for gelatinization.
[0020] Example 1
[0021] (1) Dissolve 1.5g of N,N-dimethylethanolamine in 20mL of isopropanol solvent, and add 2.3g of 1,3-propanesulfonic acid lactone dropwise under stirring. React at 40℃ for 6h. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxy sulfobetaine intermediate. (2) Add 1.3g of itaconic anhydride and 2.3g of terminal hydroxy sulfobetaine intermediate to 30mL of N,N-dimethylformamide solvent, mix well, then add 0.16g of anhydrous sodium acetate, react at 60℃ for 6h, after the reaction is completed, distill under reduced pressure, wash and dry to obtain amphoteric functional monomer. (3) Mix 35 parts by weight of acrylic acid with a neutralization degree of 65%, 8 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid and 1 part by weight of amphoteric functional monomer evenly. (4) Dissolve 20 parts by weight of cassava starch in an appropriate amount of deionized water (to make the starch mass concentration 10%), gelatinize at 70°C for 20 min, then cool to 40°C, add initiator (ammonium persulfate and sodium bisulfite, mass ratio 1:1, total amount accounting for 0.3% of the total mass of the mixed monomers), then dropwise add the mixed monomer liquid and a suspension containing 2 parts by weight of dialdehyde microcrystalline cellulose and N,N'-methylenebisacrylamide, and react at 40°C for 2 h to obtain polymerized hydrogel; The amount of N,N'-methylenebisacrylamide used accounts for 0.05% of the total mass of the mixed monomers; (5) Take 0.5 parts by weight of chitosan and dissolve it in 99.5 parts by weight of acetic acid aqueous solution with a mass concentration of 0.5% to prepare acetic acid aqueous solution with a chitosan mass concentration of 0.5% (the solution pH is 4.5-5.5). Cut the polymer hydrogel into pieces and immerse it in anhydrous ethanol to dehydrate it, so that the water content of the gel is reduced to 50%. Take it out and place it in a ventilated place to evaporate and remove the surface and shallow residual ethanol. Then immerse the dehydrated gel in the above chitosan solution (the chitosan solution completely immerses the gel), let it stand at room temperature for 1 hour, take it out and quickly rinse the surface with deionized water. After drying, the water-absorbing material product is obtained.
[0022] The drying process is a three-stage drying process, which includes: air drying at room temperature for 1 hour, vacuum drying at 40℃ (vacuum degree -0.08MPa) for 4 hours, and hot air drying at 60℃ (wind speed 1.0m / s) until constant weight. The constant weight is defined as the difference between two consecutive weighings not exceeding 0.1%.
[0023] Example 2
[0024] (1) Dissolve 1.6 g of N,N-dimethylethanolamine in 30 mL of isopropanol solvent, and add 2.4 g of 1,3-propanesulfonic acid lactone dropwise under stirring. React at 50 °C for 12 h. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxy sulfobetaine intermediate. (2) Add 2.1 g of itaconic anhydride and 4 g of terminal hydroxy sulfobetaine intermediate to 40 mL of N,N-dimethylformamide solvent, mix well, then add 0.25 g of anhydrous sodium acetate, react at 65 °C for 8 h, after the reaction is completed, distill under reduced pressure, wash and dry to obtain amphoteric functional monomer. (3) Mix 50 parts by weight of acrylic acid with a neutralization degree of 75%, 15 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid and 3 parts by weight of amphoteric functional monomer evenly. (4) Dissolve 30 parts by weight of corn starch in an appropriate amount of deionized water (to make the starch mass concentration 15%), gelatinize at 95°C for 40 min, then cool to 65°C, add initiator (ammonium persulfate and sodium bisulfite, mass ratio 1:1, total amount accounting for 0.8% of the total mass of the mixed monomers), then dropwise add the mixed monomer liquid and a suspension containing 6 parts by weight of dialdehyde microcrystalline cellulose and N,N'-methylenebisacrylamide, and react at 65°C for 4 h to obtain polymerized hydrogel; The amount of N,N'-methylenebisacrylamide used accounts for 0.15% of the total mass of the mixed monomers; (5) Take 2 parts by weight of chitosan and dissolve it in 198 parts by weight of acetic acid aqueous solution with a mass concentration of 1.0% to prepare acetic acid aqueous solution with a chitosan mass concentration of 1.0% (the solution pH is 4.5-5.5). Cut the polymer hydrogel into pieces and immerse it in anhydrous ethanol to dehydrate it, so that the water content of the gel is reduced to 70%. Take it out and place it in a ventilated place to evaporate and remove the surface and shallow residual ethanol. Then immerse the dehydrated gel in the above chitosan solution (the chitosan solution completely immerses the gel) and let it stand at room temperature for 4 hours. After taking it out, rinse the surface quickly with deionized water and dry it to obtain the finished water-absorbing material.
[0025] The drying process is a three-stage drying process, which includes: air drying at room temperature for 2 hours, vacuum drying at 40℃ (vacuum degree -0.095MPa) for 6 hours, and hot air drying at 60℃ (wind speed 2.0m / s) until constant weight. The constant weight is defined as the difference between two consecutive weighings not exceeding 0.1%.
[0026] Example 3
[0027] (1) Dissolve 1.55 g of N,N-dimethylethanolamine in 25 mL of isopropanol solvent, and add 2.35 g of 1,3-propanesulfonic acid lactone dropwise under stirring. React at 45 °C for 9 h. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxy sulfobetaine intermediate. (2) Add 1.7 g of itaconic anhydride and 3.2 g of terminal hydroxy sulfobetaine intermediate to 35 mL of N,N-dimethylformamide solvent, mix well, then add 0.2 g of anhydrous sodium acetate, react at 62 °C for 7 h, after the reaction is completed, distill under reduced pressure, wash and dry to obtain amphoteric functional monomer. (3) Mix 40 parts by weight of acrylic acid with a neutralization degree of 70%, 12 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by weight of amphoteric functional monomer evenly. (4) Dissolve 25 parts by weight of potato starch in an appropriate amount of deionized water (to make the starch mass concentration 12%), gelatinize at 85°C for 30 min, then cool to 55°C, add initiator (ammonium persulfate and sodium bisulfite, mass ratio 1:1, total amount accounting for 0.5% of the total mass of the mixed monomers), then dropwise add the mixed monomer liquid and a suspension containing 4 parts by weight of dialdehyde microcrystalline cellulose and N,N'-methylenebisacrylamide, and react at 55°C for 3 h to obtain polymerized hydrogel; The amount of N,N'-methylenebisacrylamide used accounts for 0.1% of the total mass of the mixed monomers; (5) Take 1.5 parts by weight of chitosan and dissolve it in 298.5 parts by weight of acetic acid aqueous solution with a mass concentration of 0.75% to prepare an acetic acid aqueous solution with a chitosan mass concentration of 0.5% (the solution pH is 4.5-5.5). Cut the polymer hydrogel into pieces and immerse it in anhydrous ethanol to dehydrate it, so that the water content of the gel is reduced to 60%. Take it out and place it in a ventilated place to evaporate and remove the surface and shallow residual ethanol. Then immerse the dehydrated gel in the above chitosan solution (the chitosan solution completely immerses the gel) and let it stand at room temperature for 2 hours. After taking it out, rinse the surface quickly with deionized water and dry it to obtain the finished water-absorbing material.
[0028] The drying process is a three-stage drying process, which includes: air drying at room temperature for 1.5 hours, vacuum drying at 40℃ (vacuum degree -0.09MPa) for 5 hours, and hot air drying at 60℃ (wind speed 1.5m / s) until constant weight. The constant weight is defined as the difference between two consecutive weighings not exceeding 0.1%.
[0029] Example 4
[0030] (1) Dissolve 1.52 g of N,N-dimethylethanolamine in 22 mL of isopropanol solvent, and add 2.32 g of 1,3-propanesulfonic acid lactone dropwise under stirring. React at 45 °C for 8 h. After the reaction is complete, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxy sulfobetaine intermediate. (2) Add 1.5 g of itaconic anhydride and 2.8 g of terminal hydroxy sulfobetaine intermediate to 38 mL of N,N-dimethylformamide solvent, mix well, then add 0.18 g of anhydrous sodium acetate, react at 65 °C for 7 h, after the reaction is completed, distill under reduced pressure, wash and dry to obtain amphoteric functional monomer. (3) Mix 40 parts by weight of acrylic acid with a neutralization degree of 65%, 10 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by weight of amphoteric functional monomer evenly. (4) Dissolve 22 parts by weight of cassava starch in an appropriate amount of deionized water (to make the starch mass concentration 10%), gelatinize at 75°C for 30 min, then cool to 45°C, add initiator (ammonium persulfate and sodium bisulfite, mass ratio 1:1, total amount accounting for 0.4% of the total mass of the mixed monomers), then dropwise add the mixed monomer liquid and a suspension containing 3 parts by weight of dialdehyde microcrystalline cellulose and N,N'-methylenebisacrylamide, and react at 45°C for 3 h to obtain polymerized hydrogel; The amount of N,N'-methylenebisacrylamide used accounts for 0.1% of the total mass of the mixed monomers; (5) Take 1 part by weight of chitosan and dissolve it in 199 parts by weight of 0.5% acetic acid aqueous solution to prepare a chitosan-acetic acid aqueous solution with a mass concentration of 0.5% (the solution pH is 4.5-5.5). Cut the polymer hydrogel into pieces and immerse it in anhydrous ethanol to dehydrate it, so that the water content of the gel is reduced to 55%. Take it out and place it in a ventilated place to evaporate and remove the surface and shallow residual ethanol. Then immerse the dehydrated gel in the above chitosan solution (the chitosan solution completely immerses the gel), let it stand at room temperature for 2 hours, take it out and quickly rinse the surface with deionized water. After drying, the water-absorbing material product is obtained.
[0031] The drying process is a three-stage drying process, which includes: air drying at room temperature for 1 hour, vacuum drying at 40℃ (vacuum degree -0.08MPa) for 5 hours, and hot air drying at 60℃ (wind speed 2.0m / s) until constant weight. The constant weight is defined as the difference between two consecutive weighings not exceeding 0.1%.
[0032] Example 5
[0033] (1) Dissolve 1.58 g of N,N-dimethylethanolamine in 25 mL of isopropanol solvent, and add 2.35 g of 1,3-propanesulfonic acid lactone dropwise under stirring. React at 45 °C for 10 h. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxy sulfobetaine intermediate. (2) Add 2g of itaconic anhydride and 3.8g of terminal hydroxy sulfobetaine intermediate to 35mL of N,N-dimethylformamide solvent, mix well, then add 0.24g of anhydrous sodium acetate, react at 65℃ for 8h, after the reaction is completed, distill under reduced pressure, wash and dry to obtain amphoteric functional monomer. (3) Mix 45 parts by weight of acrylic acid with a neutralization degree of 75%, 12 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid and 3 parts by weight of amphoteric functional monomer evenly. (4) Dissolve 28 parts by weight of corn starch in an appropriate amount of deionized water (to make the starch mass concentration 15%), gelatinize at 90°C for 35 min, then cool to 60°C, add initiator (ammonium persulfate and sodium bisulfite, mass ratio 1:1, total amount accounting for 0.6% of the total mass of the mixed monomers), then dropwise add the mixed monomer liquid and a suspension containing 5 parts by weight of dialdehyde microcrystalline cellulose and N,N'-methylenebisacrylamide, and react at 60°C for 4 h to obtain polymerized hydrogel; The amount of N,N'-methylenebisacrylamide used accounts for 0.15% of the total mass of the mixed monomers; (5) Take 1.5 parts by weight of chitosan and dissolve it in 148.5 parts by weight of acetic acid aqueous solution with a mass concentration of 1.0% to prepare an acetic acid aqueous solution with a chitosan mass concentration of 1.0% (the solution pH is 4.5-5.5). Cut the polymer hydrogel into pieces and immerse it in anhydrous ethanol to dehydrate it, so that the water content of the gel is reduced to 65%. Take it out and place it in a ventilated place to evaporate and remove the surface and shallow residual ethanol. Then immerse the dehydrated gel in the above chitosan solution (the chitosan solution completely immerses the gel) and let it stand at room temperature for 3 hours. After taking it out, rinse the surface quickly with deionized water and dry it to obtain the finished water-absorbing material.
[0034] The drying process is a three-stage drying process, which includes: air drying at room temperature for 2 hours, vacuum drying at 40℃ (vacuum degree -0.095MPa) for 6 hours, and hot air drying at 60℃ (wind speed 1.0m / s) until constant weight. The constant weight is defined as the difference between two consecutive weighings not exceeding 0.1%.
[0035] Comparative Example 1 The main difference between this comparative example and Example 5 is that: no amphoteric functional monomer was added, but it was replaced with an equal part by weight of acrylic acid; the other raw material types, amounts and all preparation steps are exactly the same as in Example 5.
[0036] Comparative Example 2 The main difference between this comparative example and Example 5 is that 5 parts by weight of dialdehyde microcrystalline cellulose were replaced with an equal mass of ordinary microcrystalline cellulose ultrafine powder that had not undergone sodium periodate oxidation treatment; the other raw material types, amounts, and all preparation steps were exactly the same as in Example 5.
[0037] Comparative Example 3 The main difference between this comparative example and Example 5 is that the chitosan impregnation and anchoring process is omitted; the polymerized hydrogel blocks are dehydrated with anhydrous ethanol to a water content of 65% and then directly subjected to three-stage drying without immersion in chitosan acetic acid aqueous solution; the other raw material types, amounts and preparation steps are consistent with Example 5.
[0038] Comparative Example 4 The main difference between this comparative example and Example 5 is that the drying process is changed; after the gel is impregnated with chitosan, the three-stage drying process of "room temperature drying, 40°C vacuum drying, and 60°C hot air drying" is no longer performed, but it is directly placed in an 80°C forced-air drying oven to dry to constant weight; the other pre-processes, raw material types, and amounts are exactly the same as in Example 5.
[0039] Performance testing The absorbent materials prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests. The ambient temperature for all liquid absorption performance tests was controlled at 25±2℃, and parallel test specimens were set for each sample. The average value of the test results was taken.
[0040] (1) Free swelling water absorption ratio test The free swelling water absorption ratio was determined using the tea bag method. The specific test steps were as follows: Weigh approximately 0.2 g of the absorbent material sample, accurate to 0.0001 g, and place it into a pre-weighed tea bag (nylon material, pore size ≤50 μm, dimensions 5 cm × 5 cm) and seal it; immerse the sample tea bag in excess test solution for 60 min to allow it to fully swell; remove the tea bag, hang it to drain for 10 min, and then weigh it; simultaneously, a blank control was set up, with a blank tea bag without the sample immersed, drained, and weighed under the same conditions. The free swelling water absorption ratio of the sample was tested in deionized water and 0.9% sodium chloride solution, respectively. The free swelling water absorption ratio was calculated using the following formula: FSC = (m2 - m1 - m0) / m0. In the formula: FSC is the free swelling water absorption ratio (g / g); m0 is the initial mass of the sample (g); m1 is the mass of the blank tea bag after soaking, draining, and weighing (g); m2 is the total mass of the tea bag containing the sample after soaking, draining, and weighing (g).
[0041] (2) Test of liquid absorption under pressure Referring to the test principle of pressure absorption capacity in GB / T 22875-2018 "Super Absorbent Resins for Diapers and Sanitary Napkins", this invention sets the test pressure to 0.7 psi (approximately 4.83 kPa) to simulate the absorption performance of sanitary products under high pressure conditions. The test procedure is as follows: Approximately 0.16 g of absorbent material sample is evenly spread at the bottom of a standard cylindrical sample tube with a metal mesh. A porous pressure plate is placed and weights are added to subject the sample to a pressure of 0.7 psi. The sample tube is placed in a petri dish containing excess 0.9% NaCl solution, with the mesh level with the liquid surface. After soaking for 60 minutes, the sample tube is removed, and the total mass change of the sample tube before and after absorption is measured. The pressure absorption capacity is calculated using the following formula: AUL = (m4 - m3) / m0. Where: AUL is the pressure absorption capacity (g / g); m0 is the initial mass of the sample (g); m3 is the total mass of the sample tube before absorption (g); m4 is the total mass of the sample tube after absorption (g).
[0042] (3) Simulated backflow test Referring to the backflow test principle in GB / T 8939-2018 "Sanitary Napkins (Patrolleys)", a simulated backflow test was conducted on the absorbent resin sample. The test procedure was as follows: approximately 5g of absorbent material sample was evenly spread in a non-woven bag, placed on a horizontal plate, and 50mL of 0.9% NaCl solution was poured in and allowed to stand for 3 minutes; approximately 10 layers of filter paper of known mass were covered on top of the sample, and a pressure of 0.7psi was applied and maintained for 2 minutes; the mass difference of the filter paper before and after water absorption was weighed, and this mass difference is the simulated backflow amount, in g.
[0043] (4) Chitosan binding strength test This test is a self-developed comparative test method, mainly used for horizontal relative comparison between different groups of samples, and not for arbitration detection of the absolute content of chitosan. The test procedure is as follows: Weigh approximately 1g of the absorbent material sample, place it in an Erlenmeyer flask, add 100mL of deionized water, and shake at 25℃ for 24h. After shaking, centrifuge, collect the supernatant, and determine the mass of chitosan detached from the eluent using the acidic fuchsin colorimetric method. The chitosan binding rate is calculated using the following formula: C=(M0-M1) / M0×100%. Where: C is the chitosan binding rate (%); M0 is the total mass of chitosan actually contained in 1g of finished absorbent material, determined by the acidic fuchsin colorimetric method after digestion of the original sample (g); M1 is the mass of chitosan detected in the 24h water eluent (g). A higher chitosan binding rate indicates a stronger bond between the chitosan layer and the main material.
[0044] (5) Final aerobic biodegradation rate test The test was conducted in accordance with GB / T 19277.1-2025, "Determination of the final aerobic biodegradation capacity of materials under controlled composting conditions—Method for determining the release of carbon dioxide—Part 1: General Method". The absorbent material sample was mixed with mature compost inoculum at a dry weight ratio of 1:6 and placed in a controlled composting reaction vessel. The temperature was controlled at (58±2)℃, and the moisture content of the composting system was adjusted and maintained according to the standard. The system was kept in the dark and continuously ventilated to maintain an aerobic state. The gas discharged from the reaction vessel was continuously introduced into a carbon dioxide absorption device. The device was replaced periodically at set time intervals, and the amount of carbon dioxide captured by each absorption device was measured. The cumulative CO2 release during the test period was obtained by summing the data. Another sample was taken to determine the total organic carbon content, and the theoretical CO2 release corresponding to the complete mineralization of the organic carbon in the sample was calculated accordingly. Simultaneously, microcrystalline cellulose was set as a positive reference control, and pure inoculum without the test sample was set as a blank control. Parallel samples were prepared for each group. The biodegradation rate of the positive reference material and the CO2 release of the blank inoculum met the test validity requirements specified in GB / T 19277.1-2025. The final aerobic biodegradation rate was calculated on day 45 and day 60 of the experiment, using the following formula: B = (m5 - m6) / m7 × 100%. Where: B is the final aerobic biodegradation rate (%); m5 is the cumulative CO2 release mass (g) of the sample group; m6 is the cumulative CO2 release mass (g) of the blank control group; and m7 is the theoretical CO2 release mass (g) corresponding to the complete mineralization of all organic carbon in the sample. This test characterizes the degree of mineralization of organic carbon in the sample, i.e., the proportion of carbon in the material converted into CO2 by microorganisms, which is a core indicator for determining whether the material has the ability to be "composted and degraded".
[0045] The test results are shown in Table 1.
[0046] Table 1: Performance Tests
[0047] As can be seen from Table 1, the absorbent materials prepared in Examples 1-5 of the present invention have good free swelling absorption rate of deionized water, free swelling absorption rate of physiological saline, pressure absorption capacity and degradability.
[0048] The comparison shows that Comparative Example 1, lacking the amphoteric functional monomer, exhibits significantly reduced salt tolerance and pressure-induced liquid absorption performance, while its biodegradability is similar to that of the example. Comparative Example 2, by replacing dialdehyde microcrystalline cellulose with ordinary microcrystalline cellulose, lacks aldehyde sites in the system, resulting in a substantial decrease in chitosan binding rate to 30.2%, and a simultaneous decline in water absorption and pressure-induced liquid retention performance. Comparative Example 3, by omitting the chitosan impregnation and anchoring process, shows a decrease in pressure-induced liquid absorption capacity and an increase in simulated backflow. Comparative Example 4, using a single high-temperature drying process at 80℃, results in a decrease in chitosan binding rate to 45.3%, with all indicators, including water absorption, salt tolerance, pressure-induced liquid absorption, and backflow resistance, showing significant deterioration.
[0049] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0050] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0051] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.
Claims
1. A starch-grafted biodegradable absorbent material for use in hygiene products, characterized in that, The absorbent material comprises a starch graft copolymer matrix and a chitosan layer distributed on the surface of the matrix; The starch graft copolymer is formed by free radical graft copolymerization of raw materials including natural starch, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid and amphoteric functional monomers to form a cross-linked network, and the dialdehyde microcrystalline cellulose is dispersed in the cross-linked network in the form of particles; The amphoteric functional monomer is the ring-opening esterification product of itaconic anhydride and sulfobetaine containing an alcohol hydroxyl group; The raw materials for preparing the absorbent material include, by weight: 20-30 parts of natural starch, 35-50 parts of acrylic acid, 8-15 parts of 2-acrylamido-2-methylpropanesulfonic acid, 1-3 parts of amphoteric functional monomer, 2-6 parts of dialdehyde microcrystalline cellulose, and 0.5-2 parts of chitosan. The chitosan layer is distributed on the surface of the main body after being treated with a chitosan solution; the absorbent material undergoes a three-stage drying process after being treated with the chitosan solution, the three-stage drying process including: air drying at room temperature for 1-2 hours, vacuum drying at 40℃ for 4-6 hours, and hot air drying at 60℃ to constant weight; the vacuum degree of the 40℃ vacuum drying is -0.08 to -0.095 MPa, the wind speed of the 60℃ hot air drying is 1.0-2.0 m / s, and the constant weight is the difference between two adjacent weighings not exceeding 0.1%.
2. The starch-grafted biodegradable absorbent material for hygiene products according to claim 1, characterized in that, The natural starch is selected from at least one of tapioca starch, corn starch, and potato starch.
3. The starch-grafted biodegradable absorbent material for hygiene products according to claim 1, characterized in that, The preparation method of the amphoteric functional monomer is as follows: Step 1: Dissolve N,N-dimethylethanolamine in isopropanol solvent, add 1,3-propanesulfonic acid lactone dropwise under stirring, react at 40-50℃ for 6-12h, after the reaction is completed, cool to room temperature, filter, wash and dry to obtain terminal alcohol hydroxysulfobetaine intermediate. Step 2: Add itaconic anhydride and terminal hydroxy sulfobetaine intermediate to N,N-dimethylformamide solvent, mix well, then add anhydrous sodium acetate, and react at 60-65℃ for 6-8 hours. After the reaction is completed, distill under reduced pressure, wash and dry to obtain the amphoteric functional monomer.
4. The starch-grafted biodegradable absorbent material for hygiene products according to claim 3, characterized in that, In step one, the molar ratio of N,N-dimethylethanolamine to 1,3-propanesulfonic acid lactone is 1:(1.0-1.15); in step two, the molar ratio of itaconic anhydride to the terminal hydroxy sulfobetaine intermediate is 1:(0.8-1.2); in step two, anhydrous sodium acetate is added as a catalyst, and its amount is 10.0%-15.0% of the mass of itaconic anhydride.
5. The starch-grafted biodegradable absorbent material for hygiene products according to claim 1, characterized in that, The dialdehyde microcrystalline cellulose is prepared by oxidizing microcrystalline cellulose powder (D50≤20μm) with sodium periodate at pH 3.8, and the mass ratio of microcrystalline cellulose to sodium periodate is 1:(0.5-1). The aldehyde content of the dialdehyde microcrystalline cellulose is 5.2-6.8 mmol / g.
6. A method for preparing a starch-grafted biodegradable absorbent material for hygiene products as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Preparation of mixed monomer solution: Mix acrylic acid and 2-acrylamido-2-methylpropanesulfonic acid with a neutralization degree of 65%-75% with the amphoteric functional monomer evenly; (2) Graft copolymerization: Natural starch is gelatinized at 70-95℃ for 20-40 min, then cooled to 40-65℃, an initiator is added, and then the mixed monomer liquid and the suspension containing the dialdehyde microcrystalline cellulose and the chemical crosslinking agent are added dropwise. The mixture is reacted at 40-65℃ for 2-4 h to obtain a polymer hydrogel. (3) Chitosan anchoring and drying: The polymer hydrogel is cut into pieces, dehydrated, and then immersed in a chitosan solution. After immersion, a three-stage drying process is carried out. The three-stage drying process includes air drying at room temperature for 1-2 hours, vacuum drying at 40°C for 4-6 hours, and hot air drying at 60°C until constant weight. The vacuum degree of the 40°C vacuum drying is -0.08 to -0.095 MPa, the wind speed of the 60°C hot air drying is 1.0-2.0 m / s, and the constant weight is the mass difference between two adjacent weighings not exceeding 0.1%, thus obtaining the finished water-absorbing material.
7. The method for preparing starch-grafted biodegradable absorbent material for hygiene products according to claim 6, characterized in that, In step (2), the solvent of the suspension is deionized water; the chemical crosslinking agent is N,N'-methylenebisacrylamide, and its amount accounts for 0.05%-0.15% of the total mass of the mixed monomers.
8. The method for preparing starch-grafted biodegradable absorbent material for hygiene products according to claim 6, characterized in that, The chitosan solution is an aqueous solution of acetic acid with a chitosan mass concentration of 0.5%-1.0%, wherein the acetic acid mass concentration is 0.5%-2.0%, and the solution pH is 4.5-5.5; the immersion time in the chitosan solution is 1-4 hours, and the immersion temperature is room temperature; the viscosity-average molecular weight of the chitosan is 50,000-200,000, and the degree of deacetylation is ≥85%.
9. The method for preparing starch-grafted biodegradable absorbent material for hygiene products according to claim 6, characterized in that, In step (3), the dehydration process is as follows: the polymer hydrogel is cut into pieces and then immersed in anhydrous ethanol for dehydration, so that the water content of the gel is reduced to 50%-70%.